MANAJEMEN PERUBAHAN DI LEMBAGA PEMERINTAH: STUDI KASUS IMPLEMENTASI KEBIJAKAN PELAKSANAAN PPK-BLUD DI RUMAH SAKIT JIWA PROVINSI NTB - Laksono Trisnantoro, Julastri Rondonuwu (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: NTB Mental Hospital as the only major referralcenter for mental health services in NTB was required to servethe community, to develop and be self-sufficient, while at thesame time must be able to compete in providing quality andaffordable services to the community. In order to fulfill thesedemands, since January 29, 2011 NTB Mental Hospital hasreceived full endorsement as a Mental Hospital with FinancialManagement Patterns of Local Public Service Agency (PPKBLUD).Therefore, indepth review of the implementation ofPPK-BLUD policy in NTB Provincial Mental Hospital (RSJP) isrequired.Objectives: To explore the transformation process andimplementation of PPK-BLUD policy in RSJP.Methods: The design of this study is a qualitative researchcase study to describe the dynamics of the change processand implementation of PPK-BLUD policy in RSJP.Results and Discussion: The phase of transformationprocess was not running as expected. The implementation ofPPK-BLUD policy is not optimal because some flexibility as ahospital privileges with BLUD financial pattern have not beenimplemented yet. The f inance manager was hesitant toimplement the flexible financial management and still followingthe local government financial management mechanisms. Forexternal stakeholders, the implementation of PPK-BLUD policyimplementation in RSJP did not harm local fiscal policy becausethe revenue of RSJP was still counted as revenue for localgovernment, as opposed to independent PPK-BLUD. A surveywas conducted, consisting of community satisfaction towardsthe services in RSJP, data of revenue and budgettingmanagement and distribution of fee services to employees inRSJP. The survey result described that the implementation ofPPK-BLUD policy in RSJP gives positive impacts on financial,services and benefits performances to RSJP. The positiveimpacts were an increase in the number of income, increasedof service indicators measurement and increased incentive toall employees.Conclusion: Management changes in the transformationprocess were not running optimal so that the PPK-BLUD policyin RSJP is not fully implemented, although there were someperceived positive results.Keywords: Local Public Service Agency, policy, changemanagement.